Kulit Pisang Kepok (Muca Acuminate) Menurunkan Kadar Mangan (Mn) Pada Air Sumur Gali - Raudhatul Jannah; Juanda Juanda; Hardiono Hardiono (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2020)
This type of research is experimental in nature by conducting experiments with variations in the dose of banana skin kepok. The study design used was a pre test - post test control group. Data analysis uses one way Anova statistical test with α = 0.05. The population in this study was all dug well water in the working area of the Cempaka Banjarbaru Inpatient Health Center in 2020. The results of the analysis of Manganese (Mn) decreased after treatment in each dose variation, the dose of banana peel 5 mg can reduce levels of Manganese (Mn) by 6.1% while the variation of the 25 mg dose can reduce the levels of Manganese (Mn) by 83.1 %. Based on the Anova One Way statistical test results there was no significant decrease in the value of p value (0.761)> α value (0.05). It is recommended for the community to improve the quality of well water. For related agencies, it is expected to supervise well water containing Mang.